2020
DOI: 10.3390/ijms21207787
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Crystal Structure of Chloroplastic Ribose-5-Phosphate Isomerase from Chlamydomonas reinhardtii—An Enzyme Involved in the Photosynthetic Calvin-Benson Cycle

Abstract: The Calvin–Benson cycle is the key metabolic pathway of photosynthesis responsible for carbon fixation and relies on eleven conserved enzymes. Ribose-5-phosphate isomerase (RPI) isomerizes ribose-5-phosphate into ribulose-5-phosphate and contributes to the regeneration of the Rubisco substrate. Plant RPI is the target of diverse post-translational modifications including phosphorylation and thiol-based modifications to presumably adjust its activity to the photosynthetic electron flow. Here, we describe the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 58 publications
1
7
0
Order By: Relevance
“…However, whether the upregulation of the GPD gene under salt stress can help G. uralensis reduce the production of ROS and promote the synthesis of starch and sucrose remains to be confirmed by further studies. In the regeneration stage, RPI not only isomerizes ribose-5-phosphate into ribulose-5-phosphate but also helps in the regeneration of the Rubisco substrate ( Moigne et al, 2020 ); therefore, the upregulation of the gene-encoding RPI could contribute to providing sufficient Rubisco substrates for G. uralensis seedling under salt stress. However, our results found that G2 had little effect on the gene related to carbon fixation in photosynthetic organisms in G. uralensis under salt stress.…”
Section: Discussionmentioning
confidence: 99%
“…However, whether the upregulation of the GPD gene under salt stress can help G. uralensis reduce the production of ROS and promote the synthesis of starch and sucrose remains to be confirmed by further studies. In the regeneration stage, RPI not only isomerizes ribose-5-phosphate into ribulose-5-phosphate but also helps in the regeneration of the Rubisco substrate ( Moigne et al, 2020 ); therefore, the upregulation of the gene-encoding RPI could contribute to providing sufficient Rubisco substrates for G. uralensis seedling under salt stress. However, our results found that G2 had little effect on the gene related to carbon fixation in photosynthetic organisms in G. uralensis under salt stress.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, crystal structures have been determined for RPI from a variety of different organisms such as the bacterium Escherichia coli (PDB ID: 1LKZ) ( Rangarajan et al., 2002 ), the unicellular eukaryote Saccharomyces cerevisiae (PDB ID: 1XTZ) ( Graille et al., 2005 ), the archaeon Pyrococcus horikoshii (PDB ID: 1LK5) ( Ishikawa et al., 2002 ), and numerous human parasites including the protozoan Plasmodium falciparum (PDB ID: 2F8M) ( Holmes et al., 2006 ) and the euglenoid Trypanosoma cruzi (PDB ID: 3M1P) ( Stern et al., 2011 ). In contrast, structural data of plant RPI isoforms is limited, and only the crystallographic structure of RPI from the model green alga Chlamydomonas reinhardtii (CrRPI, PDB ID: 6ZXT) has been experimentally determined ( Le Moigne et al., 2020 ).…”
Section: Structural and Biochemical Features Of Plant Ribose-5-phosph...mentioning
confidence: 99%
“…The domain is composed of a six-strand β-sheet flanked by four α-helices and is connected to the carboxy-terminal lid domain through a short β-sheet ( Figure 2B ). The lid domain is composed of a four-strand antiparallel β-sheet and two α-helices and contributes to the formation of the homo-dimeric structure, which has been validated in vitro with recombinant CrRPI ( Le Moigne et al., 2020 ).…”
Section: Structural and Biochemical Features Of Plant Ribose-5-phosph...mentioning
confidence: 99%
See 2 more Smart Citations